The role of specific helicobacter pylori virulence and host genetic factors in gastroduodenal disease - Hasan, Habsah (Pusat Pengajian Kesihatan, 2016)
The aim of this study was to determine the distribution of H. pylori virulence genes (cagA, babA2, SabA and dupA) and cagA EPIYA motifs and correlation with clinical outcomes. It also explored the presence of SNPs in genetic variants which may be associated with susceptibility or protective to H. pylori infection. H. pylori cagA, babA2, sabA and dupA genes in H. pylori dyspeptic patients were 69.5%, 41.0%, 43.8% and 22.9% respectively. Majority of Chinese patients were predominantly infected with cagA type A-B-D East Asian strain (88.9%) while cagA type A-B-C Western strain (82.8%) was predominantly detected in Indians while Malays have mixed strain. The present study identified SNPs rs3770521 (P=1.33 x’s) of XRCC5 gene, rs7042986 of SMARCA2 (P=0.0001) and rs10860808 (P=0.0002) of DRAM1 gene as susceptible SNPs to H. pylori infection among gastritis patients of Indian, Malay and Chinese respectively. This study also identified two protective SNPs rs1809578 (P=9.85x 10 ’6) of gene BANK1 and rs3776349 (P=0.0001) of gene ARHGAP26 among H. pylori gastritis patients of Indian and Malay respectively. In conclusion, the current GWAS study revealed five novel SNPs that may be associated with susceptibility and protection of H. pylori gastritis in this population.